Facilitators and barriers to completing recommended doses of pneumococcal vaccination among community-living individuals aged ≥65 years in Hong Kong - a population-based study - Zixin Wang; Yuan Fang; Margaret Ip; Mason Lau; Joseph T.F. Lau (Taylor & Francis Group, 2021)
Individuals aged ≥65 y are recommended to receive pneumococcal vaccination (PV). PV completion is defined as receiving two doses of PV among those with at least one high-risk condition for severe invasive pneumococcal diseases (IPD) or receiving one dose of PV among those without any high-risk conditions. This study investigated factors associated with PV completion among a random sample of community-living older adults in Hong Kong, China. In addition, factors associated with receiving a single dose of PV among older adults with at least one high-risk condition were also investigated. A total of 750 community-living Chinese-speaking individuals aged ≥65 y in Hong Kong (response rate: 63.4%) completed a random telephone survey from May to July 2019. PV completion was 10% among all participants. Among participants with high-risk condition(s) for severe IPD, 11.4% received a single dose of PV. After adjustment for significant background variables, several Health Belief Model constructs were significantly associated with both dependent variables: (1) perceived risk of contracting pneumococcal diseases, (2) perceived benefits of PV for protecting themselves or others, (3) perceived barriers to PV uptake, (4) being suggested by significant others to take up PV (cue to action), and (5) confidence to take up PV (perceived self-efficacy). In addition, being knowledgeable about pneumococcal diseases and vaccination, and knowing at least one peer of similar age who had taken up PV were also positively associated with both dependent variables. Targeted, theory-based health promotion efforts are needed to increase PV coverage among elderly in Hong Kong.